Assessment of food habits and Body Mass Index (BMI) among urban and rural adolescent (13-16 years of age) girls of Vijayapura district of Karnataka - Nayak, Shruti; J, Prashanth S; A, Ashwini; Jammanakatti , Savitha V (Journal of Postharvest Technology, 2022)
The present study was conducted to know the food habits among urban and rural adolescent girls of the Vijayapura district of Karnataka. Samples of  240 (120 urban and 120 rural) adolescent girls between the age group of 13-16 years were selected for the study. The self-structured questionnaire  was used for the collection of data regarding food habits among adolescent girls. The results revealed that the majority of the girls were ova-vegetarian  (42.5% urban and 50.8% rural), consume bakery products once a week (62.5% urban and 60% rural), 39.2% of urban adolescents skip meals, and an  equal percentage of (33.3%) of rural adolescent girls skip meals every day and once in a week. The results also showed that locality and skipping of  meals were significantly associated. Nearly two third of the adolescent girls (63%) had healthy weight, 16 percent were obese, 11 percent were  underweight and 10 percent were overweight. Adolescence is a growing age and the body needs more nourishment. Skipping meals every day may  hinder their growth and development as the body is at the peak of growth and development. It can further lead to undernutrition. Adolescence is the  age of puberty in which, an individual can grow to the maximum. Consumption of bakery products may influence the food habits of adolescents. So  adolescents can be given awareness regarding the importance of food in growth and development and complications of skipping meals or lower intake  of food. And also policymakers can consider these results in the future.
Keywords: Food its; adolescent girls; urban,; rural; skipping of meals; BMI